Polyacrylonitrile-based micro-nanohydrogel, preparation method and application thereof

CN122465179BActive Publication Date: 2026-10-27XIAMEN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610956009.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-27
Estimated Expiration
2046-06-30

AI Technical Summary

Technical Problem

这一方面增加了工艺步骤,另一方面洗除后的材料因缺乏增韧组分而进一步加剧了刚性脆裂的问题

Benefits of technology

(1)本申请提供的制备方法采用三乙醇胺(TEA)替代传统高毒性、强刺激性气味的四甲基乙二胺(TEMED)作为还原剂,与过硫酸铵(APS)构成氧化还原引发体系,显著提高了制备过程的安全性和环境友好性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122465179B_ABST
    Figure CN122465179B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of polyacrylonitrile-based micro-nano hydrogel, comprising the following steps: S1, dissolving ethylenic unsaturated monomers, a crosslinking agent and a surfactant in pure water to obtain a prepolymerization solution; the ethylenic unsaturated monomers comprise at least one hydrophilic ethylenic unsaturated monomer and at least one ethylenic unsaturated monomer containing a cyano group; S2, adding polyethylene glycol and an oxidation-reduction initiation system into the prepolymerization solution to obtain a mixed solution; the oxidation-reduction initiation system is ammonium persulfate / triethanolamine; S3, after the mixed solution is gelled at room temperature, the unreacted monomers and water-soluble by-products are removed by immersing in pure water for 2 hours to obtain the polyacrylonitrile-based micro-nano hydrogel; wherein the removal rate of polyethylene glycol is not more than 10%. The application also provides the hydrogel obtained by the preparation method, which has a micro-nano network structure rich in mesopores and good processing performance, and has a wide application prospect in the recovery of precious metals in electronic waste liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional polymer materials technology, specifically relating to a polyacrylonitrile-based micro / nano hydrogel, its preparation method and application, and particularly to a method for preparing a hydrogel using polyethylene glycol as both a macromolecular crowding agent and a toughening agent, as well as the hydrogel obtained by this method and its application. Background Technology

[0002] Hydrogels are three-dimensional network structures formed by cross-linking of polymers. In existing techniques for preparing hydrogels using free radical polymerization, a redox initiation system composed of ammonium persulfate (APS) and tetramethylethylenediamine (TEMED) is often used for rapid preparation at room temperature. However, TEMED has a strong, irritating odor and high toxicity, posing a threat to operator health and environmental safety with long-term use. More critically, the initiation rate of the APS / TEMED system is difficult to precisely control, resulting in a loose gel network structure with uneven pore size distribution, leading to materials with high rigidity and insufficient flexibility.

[0003] To address porosity issues, polyethylene glycol (PEG) is often introduced into the system as a porogen, but it must be washed away after polymerization. For example, Demirel et al. (Journal of Macromolecular Science, Part A, 2009, 46, 58-64) used PEG or hydroxypropyl cellulose as a porogen in the preparation of poly(N-[3-(dimethylaminopropyl)]methacrylamide-co-acrylamide) hydrogels, which had to be completely washed away after polymerization to form a porous structure. This increases the number of process steps, and the lack of toughening components in the washed-out material further exacerbates the problem of rigidity and brittleness. Furthermore, relying solely on PEG for porogenesis often results in macroporous structures, leading to an imbalance in specific surface area and active site density, making it difficult to achieve precise structural control at the micro / nano scale.

[0004] Therefore, there is an urgent need to develop a hydrogel preparation method that can avoid the use of highly toxic initiators, achieve fine control of network structure, and simplify process steps. Summary of the Invention

[0005] The purpose of this application is to provide a method for preparing polyacrylonitrile-based micro / nano hydrogels based on macromolecular crowding effects, as well as the hydrogels obtained by this method and their applications.

[0006] To achieve the above objectives, this application provides the following technical solution: A method for preparing a polyacrylonitrile-based micro / nano hydrogel includes the following steps: S1. Dissolve the olefinic unsaturated monomer, crosslinking agent, and surfactant in pure water to obtain a prepolymerization solution; the olefinic unsaturated monomer includes at least one hydrophilic olefinic unsaturated monomer and at least one cyano-containing olefinic unsaturated monomer. S2. Polyethylene glycol and a redox initiation system are added to the prepolymerization solution to obtain a mixed solution; the redox initiation system is ammonium persulfate / triethanolamine. S3. After gelling the mixed solution at room temperature, soak it in pure water for 2 hours to remove unreacted monomers and water-soluble byproducts to obtain the polyacrylonitrile-based micro / nano hydrogel; wherein the polyethylene glycol removal rate does not exceed 10%.

[0007] This application also provides the following technical solutions: Polyacrylonitrile-based micro / nano hydrogels obtained by the aforementioned preparation method.

[0008] This application also provides the following technical solutions: The aforementioned polyacrylonitrile-based micro / nano hydrogels are used in the preparation of adsorbents; the adsorbents are used for the recovery of precious metals from electronic waste leachate.

[0009] The technical solution provided in this application has the following beneficial effects: (1) The preparation method provided in this application uses triethanolamine (TEA) instead of the traditional highly toxic and strongly irritating tetramethylethylenediamine (TEMED) as a reducing agent, and forms a redox initiation system with ammonium persulfate (APS), which significantly improves the safety and environmental friendliness of the preparation process.

[0010] (2) The preparation method provided in this application uses polyethylene glycol (PEG) as a macromolecular congestion agent. Through the physical confinement effect generated by its polymer chain, the reaction space is divided into a large number of micro and nano reaction regions, which effectively inhibits the growth and aggregation of large particles, thereby obtaining a micro and nano network structure hydrogel with smaller particle size, more uniform distribution and rich mesoporous structure.

[0011] (3) The PAG hydrogel provided in this application, thanks to the fine network structure induced by the above-mentioned confinement effect, has a BET specific surface area of ​​up to 18.42 m². 2 / g, significantly higher than that of hydrogels prepared by the APS / TEMED system (8.05 m). 2 / g), which helps to expose more active adsorption sites.

[0012] (4) The PAG hydrogel provided in this application retains most of the PEG used in the preparation process inside the three-dimensional network, so that PEG can play the dual role of macromolecular crowding agent and toughening agent, ensuring that the hydrogel has a fine micro-nano network structure and good processing performance, overcoming the defects of hydrogels prepared by traditional methods that are rigid and brittle.

[0013] (5) The PAG hydrogel provided in this application, after being modified by amine oxime esterification, can be used as an adsorbent, exhibiting excellent adsorption capacity for gold ions, and has broad application prospects in the recovery of precious metals in complex systems such as electronic waste liquid. Thanks to the toughening effect of PEG, the adsorbent is easy to process and mold; after processing and molding and putting it into use, the PEG can be gradually eluted by the solution during the precious metal recovery process, leaving a large number of pores in situ, thereby further improving the adsorption performance. This flexible PEG retention strategy simplifies process control and enhances the reliability of adsorbent preparation and use. Attached Figure Description

[0014] Figure 1 SEM images of the hydrogel in its dry state (left, PAG-0.5; right, PAT).

[0015] Figure 2 The images show the nitrogen adsorption-desorption isotherm (left) and pore size distribution curve (right).

[0016] Figure 3 The storage modulus-frequency scan curve is shown for the dry state of the hydrogel.

[0017] Figure 4 The strain scan curve of PAG-2 hydrogel is shown.

[0018] Figure 5 The self-healing curve of PAG-2 hydrogel is shown.

[0019] Figure 6 This is a picture of the PDG adsorbent after it has adsorbed precious metals.

[0020] Figure 7 A bar chart showing the changes in the concentration of various ions before and after the adsorption of precious metals by the PDG adsorbent. Invention Details 1. Terminology Explanation All patents and other publications cited herein are incorporated herein in their entirety. In the event of any conflict between any description of terminology herein and any document incorporated herein by reference, this document shall prevail.

[0022] Numerical ranges can be represented by a hyphen "-" or a tilde "~". Unless otherwise stated, the range should be understood to encompass both the endpoint values ​​and any values ​​in between. There are no particular restrictions on the type of numeric values ​​within the range, including but not limited to integers, decimals, fractions, percentages, etc., unless explicitly excluded by the context or a particular numeric type is technically unavailable. The type of numeric values ​​within the range is not limited by the specific representation of the endpoints.

[0023] The terms “including,” “containing,” and similar expressions have a non-restrictive meaning.

[0024] The terms "optional" and similar expressions are used to indicate that a certain feature (including but not limited to components, steps, parameters or structures) may be present in some embodiments but not in others, thereby providing technical flexibility for different implementations without departing from the core concept of the present invention.

[0025] "Any combination" of the enumeration items means any two or more of the enumeration items that coexist or are used together, including but not limited to any two combinations, any three combinations, any more items, and combinations of all the enumeration items, unless the context explicitly excludes it or a particular combination is technically impossible.

[0026] The use of labels such as a), b), i), ii), 1), 2), S1, S2, etc. to number the steps of a method is only for the convenience of description and reading, and does not mean that the corresponding steps must be performed in the order of the numbers, unless the text explicitly states or the information in the text can be clearly inferred that there is a logical or temporal relationship between specific steps.

[0027] When the unit of molecular weight is not specified, it is expressed in Daltons (Da) by default.

[0028] The "polyacrylonitrile-based micro / nano hydrogels" described in this article refer to hydrogel materials whose polymer network contains at least one cyano-containing olefinic unsaturated monomer. The term "micro / nano" refers to the multi-layered network structure of the hydrogel in its dry state, ranging from micrometers to nanometers in size. Specifically, it manifests as a three-dimensional network structure with abundant mesopores (2-50 nm) formed by the assembly of uniformly sized, narrowly distributed polymer particles (typically micrometer-scale). Polyacrylonitrile-based micro / nano hydrogels combine the chemical reactivity provided by polyacrylonitrile segments (e.g., for use in amine oxime modification) with the high specific surface area and rapid mass transfer capabilities imparted by the micro / nano network structure.

[0029] The term "pure water" as used in this article refers to water with a resistivity of not less than 1 MΩ·cm at 25°C, including but not limited to deionized water, distilled water, and ultrapure water.

[0030] The term "olefinic unsaturated monomer" as used herein refers to a small molecule compound containing at least one polymerizable carbon-carbon double bond (>C=C<). The type of polymerization reaction is not particularly limited, and includes, but is not limited to, free radical polymerization, ionic polymerization, coordination polymerization, or other polymerization reactions.

[0031] The term "hydrophilic olefinic unsaturated monomer" as used herein refers to an olefinic unsaturated monomer whose homopolymer, after reaching water absorption equilibrium in deionized water at 25°C, has a water absorption rate of not less than 10 wt%. Preferably, the hydrophilic olefinic unsaturated monomer contains at least one hydrophilic group. Exemplary hydrophilic groups include, but are not limited to, hydroxyl, carboxyl, amide, amino, sulfonic acid, phosphate, quaternary ammonium salt, betaine, and polyether segments. Exemplary hydrophilic olefinic unsaturated monomers include, but are not limited to, acrylic acid, methacrylic acid, acrylamide, methacrylamide, etc. N -Isopropylacrylamide, N -[tris(hydroxymethyl)methyl]acrylamide, N , N -Diethylacrylamide, N , N -Dimethylacrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate N -Vinylpyrrolidone, N -Vinylcaprolactam, methacryloyloxyethyltrimethylammonium chloride, methacrylamidopropyltrimethylammonium chloride, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonylpropyl)ammonium hydroxide, 3-[(3-acrylamidopropyl)dimethylammonium]propionate, etc.

[0032] The term "hydrophobic olefinic unsaturated monomer" as used herein refers to an olefinic unsaturated monomer whose homopolymer has a water absorption rate of less than 10 wt% after reaching water absorption equilibrium in deionized water at 25°C. Exemplary hydrophobic olefinic unsaturated monomers include, but are not limited to, styrene, α-methylstyrene, p-methylstyrene, vinyl chloride, vinylidene chloride, ethylene, propylene, isobutylene, vinyl acetate, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, lauryl methacrylate, stearyl methacrylate, vinyltrimethylsilane, vinyltrimethoxysilane, vinyltriethoxysilane, 1,3-butadiene, isoprene, etc.

[0033] The term "cyano-containing olefinic unsaturated monomer" as used herein refers to an olefinic unsaturated monomer containing at least one cyano group (–C≡N). Exemplary cyano-containing olefinic unsaturated monomers include, but are not limited to, acrylonitrile, methacrylonitrile, methyl cyanoacrylate, ethyl cyanoacrylate, butyl cyanoacrylate, isooctyl cyanoacrylate, etc.

[0034] The term "polyene unsaturated crosslinking agent" as used herein refers to a compound containing at least two polymerizable carbon-carbon double bonds per molecule. This polyene unsaturated crosslinking agent can undergo crosslinking copolymerization with one or more olefinic unsaturated monomers, forming chemical crosslinking points between polymer chains to construct a three-dimensional network structure. Preferably, each molecule of the polyene unsaturated crosslinking agent contains 2 to 10 polymerizable carbon-carbon double bonds. Exemplary polyene unsaturated crosslinking agents include, but are not limited to, those mentioned above. N , N' -methylenebisacrylamide, N , N' - Methylene dimethacrylamide, ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, divinylbenzene, triallyl isocyanurate, triallylamine, tetraallyl ethylenediamine, diallyl phthalate, etc.

[0035] The term "polyethylene glycol" (PEG) as used herein refers to a polyether compound composed of repeating structural units (-CH2CH2O-). Unless otherwise specified, the polyethylene glycol may be monodisperse or polydisperse. Unless otherwise specified, under the hydrogel preparation conditions provided in this application, the polyethylene glycol acts as a macromolecular crowding agent and essentially does not participate in chemical reactions; under this premise, there are no particular limitations on the end group type of the polyethylene glycol, including but not limited to -OH, -OMe, -OEt, -OBn, etc.

[0036] The "macromolecule congesting agent" described herein refers to a macromolecule that can alter the microenvironment of a reaction system through its spatial confinement effect. Under the hydrogel preparation conditions provided in this application, the mechanism of action of the macromolecule congesting agent includes: increasing the local macromolecule concentration, restricting molecular diffusion, regulating the spatial distribution of reactants, and influencing polymerization kinetics, thereby dividing the reaction system into multiple micro-reaction regions and promoting the formation of a more uniform and refined polymer network structure.

[0037] The term "PEG removal rate" as used herein refers to the percentage of PEG mass eluted from the hydrogel after gelation and immersion in pure water, relative to the initial added mass. Conversely, "PEG retention rate" refers to the percentage of PEG mass remaining within the hydrogel after washing. Unless otherwise specified, the removed PEG mass is obtained by analyzing the PEG content in the eluent. This content analysis can be performed using methods conventional in the art, including but not limited to liquid chromatography, gel permeation chromatography, and colorimetry.

[0038] The "redox initiation system" described herein refers to an initiator combination consisting of at least one oxidant and at least one reductant, capable of generating active free radicals through a single-electron transfer reaction. The oxidant includes, but is not limited to, one or more of ammonium persulfate, potassium persulfate, sodium persulfate, hydrogen peroxide, benzoyl peroxide, and tert-butyl hydroperoxide; the reductant includes, but is not limited to, one or more of tertiary amines, sodium bisulfite, sodium thiosulfate, ferrous salts, and ascorbic acid. Exemplary tertiary amine reductants include, but are not limited to, tetramethylethylenediamine (TEMED) and triethanolamine (TEA). N , N , N' , N' -Tetramethyl-1,3-propanediamine, etc. Exemplary redox initiation systems include, but are not limited to, ammonium persulfate / triethanolamine, potassium persulfate / triethanolamine, ammonium persulfate / tetramethylethylenediamine, ammonium persulfate / sodium bisulfite, hydrogen peroxide / ascorbic acid, etc.

[0039] The term "surfactant" as used herein refers to amphiphilic compounds whose molecular structure contains both hydrophilic and hydrophobic portions. Surfactants can be used to promote the uniform dispersion or emulsification of hydrophobic compounds in an aqueous phase, ensuring the homogeneity and stability of the prepolymer solution and providing a uniform reaction environment. Exemplary surfactants include, but are not limited to, sodium dodecyl sulfate (SDS), sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide (CTAB), Tween series (such as Tween-20, Tween-80), Span series (such as Span-60, Span-80), Triton X-100, and poloxamer.

[0040] Unless otherwise specified, all polymer molecular weights provided in this article are number average molecular weights (M). n ).

[0041] The "polydispersity index" (PDI) mentioned in this article refers to the weight-average molecular weight (Mb) of the polymer. w ) and number-average molecular weight (M n The ratio of PDI to M, i.e., PDI = M w / M n The closer the PDI is to 1, the narrower the molecular weight distribution of the polymer; the larger the PDI, the wider the molecular weight distribution of the polymer. In principle, when the PDI equals 1, it can be considered a completely monodisperse polymer; when the PDI is greater than 1, it can be considered a polydisperse polymer. For practical polymer systems, polymers with a PDI close to 1 (e.g., not higher than 1.005) are usually also called monodisperse polymers.

[0042] The "mercapto-oxime modification" described in this article refers to the chemical modification process of converting cyano groups on the side chains or main chains of polymers into mechano-oxime groups (-C(=NOH)NH2) through a chemical reaction. Mercapto-oxime groups possess unique metal chelating capabilities and can be used to recover precious metals from complex systems such as electronic waste leachate and industrial wastewater. The mechano-oxime modification of polyacrylonitrile-based hydrogels aims to introduce precious metal-specific adsorption sites into their polymer network, endowing the material with highly efficient precious metal adsorption and separation capabilities.

[0043] 2. Implementation Plan One embodiment of this application is as follows: A method for preparing a polyacrylonitrile-based micro / nano hydrogel includes the following steps: S1. Dissolve the olefinic unsaturated monomer, crosslinking agent, and surfactant in pure water to obtain a prepolymerization solution; the olefinic unsaturated monomer includes at least one hydrophilic olefinic unsaturated monomer and at least one cyano-containing olefinic unsaturated monomer. S2. Add polyethylene glycol and redox initiation system to the prepolymerization solution to obtain a mixed solution; S3. After gelling the mixed solution, soak it in pure water for 2 hours to remove unreacted monomers and water-soluble byproducts to obtain the polyacrylonitrile-based micro / nano hydrogel; wherein the polyethylene glycol removal rate does not exceed 10%.

[0044] In some specific embodiments, the hydrophilic olefinic unsaturated monomer is acrylic acid, methacrylic acid, acrylamide, or methacrylamide. N -Isopropylacrylamide, N -[tris(hydroxymethyl)methyl]acrylamide, N , N -Diethylacrylamide, N , N -Dimethylacrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate N -Vinylpyrrolidone, N - Vinylcaprolactam, methacryloyloxyethyltrimethylammonium chloride, methacrylamidopropyltrimethylammonium chloride, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonylpropyl)ammonium hydroxide, 3-[(3-acrylamidopropyl)dimethylammonium]propionate or any combination thereof.

[0045] In some specific embodiments, the cyano-containing olefinic unsaturated monomer is acrylonitrile, methacrylonitrile, methyl cyanoacrylate, ethyl cyanoacrylate, butyl cyanoacrylate, isooctyl cyanoacrylate, or any combination thereof.

[0046] In some specific embodiments, the olefinic unsaturated monomer further includes at least one hydrophobic olefinic unsaturated monomer; preferably, the hydrophobic olefinic unsaturated monomer is styrene, α-methylstyrene, p-methylstyrene, vinyl chloride, vinylidene chloride, ethylene, propylene, isobutylene, vinyl acetate, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, lauryl methacrylate, stearyl methacrylate, vinyltrimethylsilane, vinyltrimethoxysilane, vinyltriethoxysilane, 1,3-butadiene, isoprene, or any combination thereof.

[0047] In some specific embodiments, the crosslinking agent is a polyene unsaturated crosslinking agent, preferably... N , N' -methylenebisacrylamide, N , N' - Methylene dimethacrylamide, ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, divinylbenzene, triallyl isocyanurate, triallylamine, tetraallyl ethylenediamine, diallyl phthalate, or any combination thereof.

[0048] In some specific embodiments, the surfactant is sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, Tween-20, Tween-80, Span-60, Span-80, Triton X-100, poloxamer, or any combination thereof.

[0049] In some specific implementations, the amount of the surfactant is 0.1% to 10% of the total mass of the olefin unsaturated monomers.

[0050] In some specific implementations, the polyethylene glycol is monodisperse or polydisperse, with the structure RO-(CH2CH2O). n -OR; where n is the degree of polymerization, selected from any integer between 4 and 20; each R is independently a hydrogen atom, methyl, ethyl, or benzyl.

[0051] In some specific embodiments, the number average molecular weight of the polyethylene glycol is 400-1000 Da.

[0052] In some specific implementations, the amount of polyethylene glycol used is 10% to 40% of the total mass of the olefinic unsaturated monomers.

[0053] In some specific implementations, the redox initiation system is ammonium persulfate / triethanolamine, potassium persulfate / triethanolamine, ammonium persulfate / sodium bisulfite, or hydrogen peroxide / ascorbic acid.

[0054] In some specific implementations, the molar ratio of oxidant to reductant in the redox initiation system is (0.1-100):(0.1-100), preferably 1:32.6.

[0055] In some specific implementations, the gelation is performed at room temperature.

[0056] In some specific embodiments, the molar ratio of the hydrophilic olefinic unsaturated monomer, the cyano-containing olefinic unsaturated monomer, and the crosslinking agent is (0.1-2):(1.5-2.5):(0.005-0.01), preferably 1:2.17:0.0074.

[0057] In some specific implementations, step S3 also includes a drying step after soaking.

[0058] In some specific implementations, the drying process is freeze drying, vacuum drying, or atmospheric pressure drying.

[0059] Another implementation scheme of this application is as follows: A polyacrylonitrile-based micro / nano hydrogel, obtained by any of the aforementioned preparation methods.

[0060] In some specific embodiments, the specific surface area of ​​the hydrogel in the dry state is 15-25 m². 2 / g.

[0061] Another implementation scheme of this application is as follows: Application of any of the aforementioned polyacrylonitrile-based micro / nano hydrogels in adsorbent preparation.

[0062] In some specific implementations, the application includes: modifying the polyacrylonitrile-based micro / nano hydrogel by amination oxime to obtain an adsorbent; the adsorbent is used for the recovery of precious metals from electronic waste leachate. Detailed Implementation

[0063] The raw materials used in this application can be purchased or synthesized in-house. The following specific embodiments are used to further describe the implementation of the present invention and do not limit the scope of the invention.

[0064] Example 1 Acrylamide (0.5 g, 7.0 mmol), acrylonitrile (1 mL, 15.2 mmol), and... N , N’Methylenebisacrylamide (0.008 g, 0.052 mmol) and sodium dodecyl sulfate (0.02 g, 0.069 mmol) were dissolved in 4 mL of deionized water and mixed thoroughly with magnetic stirring to obtain a clear prepolymerization solution. Ammonium persulfate (APS, 0.01 g, 0.044 mmol) was added to this solution, followed by α,ω-dihydroxy polyethylene glycol (0.31 mL, 0.52 mmol; M...) under rapid stirring. n A mixture of 600 Da (PDI=1.1) and triethanolamine (TEA, 0.19 mL, 1.43 mmol) (total 0.5 mL) was prepared to obtain a mixed solution. The mixed solution was rapidly transferred to a glass mold and allowed to stand at room temperature (25°C) until the system lost its fluidity, forming a self-supporting hydrogel. The resulting hydrogel was immersed in deionized water for 2 hours to remove unreacted monomers and soluble byproducts, yielding a hydrogel (denoted as PAG-0.5).

[0065] Example 2 In this embodiment, the following control group was set up, and the gelation time was recorded (starting from the time the initiation system was added).

[0066] Control group 1: Following the preparation method of Example 1, without using PEG, and replacing TEA with TEMED, with the other conditions remaining the same, a hydrogel (denoted as PAT) was obtained.

[0067] Control group 2: The preparation method of Example 1 was followed, but without PEG, and all other conditions were the same.

[0068] Control group 3: The preparation method of Example 1 was followed, but TEA and PEG were not used, and all other conditions were the same.

[0069] Control group 4: The preparation method of Example 1 was followed, but APS and PEG were not used, and all other conditions were the same.

[0070] Control group 5: The preparation method of Example 1 was followed, but APS and PEG were not used, and TEA was replaced with TEMED, with the other conditions remaining the same.

[0071] Control group 6: The preparation method of Example 1 was followed, but APS and TEA were not used, and all other conditions were the same.

[0072] Table 1. Results of the gelation test

[0073] The gelation test results (Table 1) show that the redox initiation system (APS / TEA or APS / TEMED) is a necessary condition for the gelation reaction to occur; gelation cannot occur without any initiating component (control groups 3-6). Both Example 1 and Control Group 2 gelled within approximately 5 minutes, but the gelation time of Example 1 (5 minutes 02 seconds) was slightly longer than that of Control Group 2 (4 minutes 49 seconds) without PEG. This is because PEG, as a macromolecular congestor, creates a confinement effect through its polymer chains, hindering the free diffusion of free radicals and monomers, forcing the polymerization reaction to occur within a confined space, thus slightly prolonging the gelation time. Control Group 1, which used TEMED instead of TEA, had a significantly longer gelation time (5 minutes 26 seconds) than both Example 1 and Control Group 2, indicating that TEA can effectively improve the initiation efficiency of this polymerization system.

[0074] Example 3 The PAG-0.5 hydrogel prepared in Example 1 and the PAT hydrogel prepared in Control Group 1 were freeze-dried separately, and their morphology was observed using scanning electron microscopy (SEM). Results ( Figure 1 The results show that the introduction and retention of PEG significantly affect the microstructure of the hydrogel. In PAT hydrogels, due to the lack of spatial confinement by PEG, the polymerization reaction occurs in a homogeneous solution, and the diffusion of free radicals and monomers is unrestricted, leading to disordered aggregation of polymer particles during growth, ultimately forming a large-particle network structure with uneven size and severe agglomeration. In contrast, in the PAG hydrogel of this invention, PEG acts as a macromolecular crowding agent, and its polymer chains generate a strong confinement effect within the polymerization system, dividing the reaction space into numerous independent reaction regions at the micro- and nano-scale. This confined space forces monomer polymerization and particle growth to occur within a limited range, effectively suppressing disordered aggregation between particles, thereby forming a three-dimensional network structure with significantly reduced particle size, uniform distribution, and greater density. This microstructure characteristic is direct morphological evidence of the macromolecular crowding effect and provides a structural basis for the hydrogel's high specific surface area and excellent adsorption performance.

[0075] Example 4 The pore structure of the PAG hydrogel in Example 1 and the PAT hydrogel in Control Group 1 was analyzed using nitrogen adsorption-desorption method. The results are as follows: Figure 2 As shown, the PAT hydrogel has a low nitrogen adsorption capacity and a BET specific surface area of ​​only 8.05 m². 2 / g; while PAG hydrogel exhibits a typical type IV adsorption isotherm and a distinct hysteresis loop in the high relative pressure region, indicating that it contains abundant mesoporous structure, with a BET specific surface area of ​​18.42 m². 2 / g. The pore size distribution curve further shows that the PAG hydrogel has a wider pore distribution and a more developed pore structure in the mesoporous region.

[0076] Example 5 Referring to the preparation method of Example 1, the amount of the mixture of PEG and TEA was changed to 1 mL (wherein the volume ratio of PEG / TEA is 1.6:1), and the other conditions remained unchanged, to obtain PAG-1 hydrogel.

[0077] Referring to the preparation method of Example 1, the amount of the mixture of PEG and TEA was changed to 2 mL (where the volume ratio of PEG / TEA was 1.6:1), and the other conditions remained unchanged, to obtain PAG-2 hydrogel.

[0078] Referring to the preparation method of Example 1, the hydrogel cleaning step was changed to: soaking the obtained hydrogel in deionized water for 2 days, changing the water every 8 hours, while keeping the other conditions unchanged, to obtain PAG-Ex hydrogel.

[0079] Calculate the PEG removal rate (%) using the following formula: PEG removal rate = [1 (dry gel mass) [Theoretical polymer network quality / total PEG feed] × 100%; Wherein, the dry gel mass is the mass of the hydrogel after freeze-drying; the theoretical polymer network mass is the total amount of monomers, crosslinking agents and surfactants added in each formulation; The PEG removal rates of PAG-0.5, PAG-1, and PAG-2 hydrogels were measured to be 5.6%, 7.3%, and 9.2%, respectively, all below 10%, while the PEG removal rate of PAG-Ex was close to 100%. See Table 2 for details.

[0080] Table 2. Results of PEG Removal Rate Measurement

[0081] After freeze-drying the hydrogels of control group 2 (without PEG), PAG-0.5 hydrogel from Example 1, and PAG-1 and PAG-2 hydrogels from this example, frequency scanning tests were performed. The results are as follows: Figure 3 As shown, the storage modulus (G') of the hydrogel gradually increases with the increase of PEG / TEA content, indicating that its structural stability is significantly enhanced.

[0082] Strain scanning tests were performed on the PAG-2 hydrogel. Results ( Figure 4The results showed that within the strain scanning range of 0.0001% to 1%, its storage modulus (G') was consistently greater than its loss modulus (G''), exhibiting a wide linear viscoelastic region. When the strain increased to approximately 1%, G' and G'' intersected, and the hydrogel structure was disrupted. This result fully validates that the PAG hydrogel possesses a certain degree of deformation resistance. Its self-healing performance was further evaluated using alternating strain scanning tests. During the test, the strain was switched between 0.01% and 1000% every minute to intermittently disrupt the gel structure. Results ( Figure 5 The results showed that the storage modulus (G') and loss modulus (G'') did not decrease significantly within three cycles, indicating that the hydrogel has a certain self-healing ability and structural stability.

[0083] Example 6 This embodiment prepares an adsorbent based on PAG hydrogel and verifies its adsorption performance.

[0084] The PAG hydrogel prepared in Example 1 was freeze-dried and then immersed in a 0.5 mol / L hydroxylamine hydrochloride solution. The pH of the solution was adjusted to 7 with sodium hydroxide, and the reaction was carried out in an 80°C water bath for 8 hours to perform amination oxime modification, which converted the cyano groups (-CN) in the hydrogel network into amination oxime groups (-C(=NOH)NH2), thereby introducing adsorption sites with specific chelating effects on noble metal ions. After the reaction was completed, the hydrogel was removed, repeatedly rinsed with deionized water until neutral, and then freeze-dried again to obtain the amination oxime-modified PAG hydrogel adsorbent (denoted as PDG).

[0085] To simulate a real electronic waste liquid environment, a solution containing gold ions (Au(III), 3.56 mg / L) and various coexisting interfering metal ions (including Zn) was prepared. 2+ Ni 2+ Cu 2+ Fe 3+ Al 3+ A mixed solution of PDG adsorbent with concentrations of 0.546 mg / L, 13.8 mg / L, 25.2 mg / L, 17.6 mg / L, and 0.977 mg / L was placed in a container. The PDG adsorbent was then directly immersed in the simulated waste liquid and shaken at room temperature until adsorption equilibrium was reached. Figure 6 This is a picture of the actual object after adsorption. Figure 7 The values ​​represent the changes in ion concentrations before and after adsorption. The results show that the PDG adsorbent exhibits significant adsorption selectivity for gold ions and possesses the ability to efficiently recover noble metals under complex ionic conditions.

[0086] All equivalent structural or procedural transformations made using the content of this application's specification, directly or indirectly applied to the same or related technical fields as this application, are included within the scope of patent protection of this application. For those skilled in the art, this invention can be implemented in a wide range with equivalent parameters, formulations, and conditions without departing from its spirit and scope, and without the need for unnecessary experimentation. Although this application includes specific conditions in its embodiments, it should be understood that the conditions of each embodiment can be combined in any suitable manner where technically feasible. To avoid unnecessary repetition, this application will not further describe the various possible combinations. In summary, any changes, modifications, substitutions, and variations made using conventional techniques known in the art based on the principles of this invention are considered to be disclosed in this application.

Claims

1. A method for preparing a polyacrylonitrile-based micro / nano hydrogel, comprising the following steps: S1. Dissolve the olefinic unsaturated monomer, crosslinking agent, and surfactant in pure water to obtain a prepolymerization solution; the olefinic unsaturated monomer includes at least one hydrophilic olefinic unsaturated monomer and at least one cyano-containing olefinic unsaturated monomer. S2. Polyethylene glycol and a redox initiation system are added to the prepolymerization solution to obtain a mixed solution; the redox initiation system is ammonium persulfate / triethanolamine; the amount of polyethylene glycol used is 10% to 40% of the total mass of the olefinic unsaturated monomers; S3. After gelling the mixed solution at room temperature, soak it in pure water for 2 hours to remove unreacted monomers and water-soluble byproducts to obtain the polyacrylonitrile-based micro / nano hydrogel; wherein the polyethylene glycol removal rate does not exceed 10%.

2. The method for preparing polyacrylonitrile-based micro / nano hydrogels according to claim 1, characterized in that, The hydrophilic olefinic unsaturated monomer is acrylic acid, methacrylic acid, acrylamide, or methacrylamide. N -Isopropylacrylamide, N -[tris(hydroxymethyl)methyl]acrylamide, N , N -Diethylacrylamide, N , N -Dimethylacrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate N -Vinylpyrrolidone, N - Vinylcaprolactam, methacryloyloxyethyltrimethylammonium chloride, methacrylamidopropyltrimethylammonium chloride, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonylpropyl)ammonium hydroxide, 3-[(3-acrylamidopropyl)dimethylammonium]propionate or any combination thereof.

3. The method for preparing polyacrylonitrile-based micro / nano hydrogels according to claim 1, characterized in that, The cyano-containing olefinic unsaturated monomer is acrylonitrile, methacrylonitrile, methyl cyanoacrylate, ethyl cyanoacrylate, butyl cyanoacrylate, isooctyl cyanoacrylate, or any combination thereof.

4. The method for preparing polyacrylonitrile-based micro / nano hydrogels according to claim 1, characterized in that, The crosslinking agent is a polyene unsaturated crosslinking agent, specifically... N , N' -methylenebisacrylamide, N , N' - Methylene dimethacrylamide, ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, divinylbenzene, triallyl isocyanurate, triallylamine, tetraallyl ethylenediamine, diallyl phthalate, or any combination thereof.

5. The method for preparing polyacrylonitrile-based micro / nano hydrogels according to claim 1, characterized in that, The surfactant is sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, Tween-20, Tween-80, Span-60, Span-80, Triton X-100, poloxamer, or any combination thereof.

6. The method for preparing polyacrylonitrile-based micro / nano hydrogels according to claim 1, characterized in that, The polyethylene glycol is monodisperse or polydisperse, and its structure is RO-(CH2CH2O). n -OR; where n is the degree of polymerization, selected from any integer between 4 and 20; each R is independently a hydrogen atom, methyl, ethyl, or benzyl.

7. The method for preparing polyacrylonitrile-based micro / nano hydrogels according to claim 1, characterized in that, The molar ratio of the hydrophilic olefinic unsaturated monomer, the cyano-containing olefinic unsaturated monomer, and the crosslinking agent is (0.1-2):(1.5-2.5):(0.005-0.01).

8. The method for preparing polyacrylonitrile-based micro / nano hydrogels according to claim 1, characterized in that, Step S3 also includes a drying step after soaking.

9. A polyacrylonitrile-based micro / nano hydrogel, obtained by the preparation method described in claim 1.

10. The application of the polyacrylonitrile-based micro / nano hydrogel according to claim 9 in the preparation of adsorbents, characterized in that, The applications include: modifying the polyacrylonitrile-based micro / nano hydrogel by ammonia oxime to obtain an adsorbent; the adsorbent is used for the recovery of precious metals from electronic waste leachate.

Citation Information

Patent Citations

  • Thermo-sensitive polyamidoxime hydrogel, preparation method and application of thermo-sensitive polyamidoxime hydrogel in uranium adsorption

    CN116478426A

  • High-performance acrylate emulsion and preparation method thereof

    CN119390907A